Financial Analysis of Handline Tuna Fishing Units in Cilacap Ocean Fishing Port - Central Java - Aryanda, Rico Evan; Perangin-angin, Robet; Suharyanto, Suharyanto; Haris, Dendi; Sutono, Dian; Hermawan, Maman; Goenaryo, Goenaryo (Politeknik Kelautan dan Perikanan Karawang, 2023)
The purpose of this study is to determine the feasibility of the tuna handline business on ships based at the Cilacap Ocean Fisheries Port (PPS), Central Java. The financial analysis uses 6 indicators in determining business feasibility, including R/C Ratio, B/C Ratio, Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and ROI (Return On Investment). Financial analysis based on 6 financial indicators obtained values including an R/C Ratio of 1.49, Payback Period (PP) for 4 years, Return On Investment (ROI) of 2.4%, Net Present Value (NPV) of IDR 3,738,751,559, B/C Ratio of 3.57 and Internal Rate of Return (IRR) of 48.2%. So that it can be stated that the tuna handline business is financially feasible.